The Culex Mosquitoes (Diptera: Culicidae) of French Guiana: A Comprehensive Review With the Description of Three New Species. Issue 1 (3rd December 2020) - Talaga, Stanislas; Duchemin, Jean-Bernard; Girod, Romain; Dusfour, Isabelle
Abstract: The taxonomically intricate genus Culex Linnaeus includes numerous known vector species of parasites and viruses to humans. The aim of this article is to comprehensively review the Culex species which occur in French Guiana to provide a stronger taxonomic foundation for future studies on this genus in South America. The occurrence of Culex species was investigated in light of current taxonomic knowledge through an extensive examination of voucher specimens deposited in the entomological collections of four French depositories and additional specimens recently collected at various localities in French Guiana. Based on this review, 104 Culex species classified in eight subgenera are confirmed to occur in French Guiana. Compared to the most recent checklist, 18 species are added, and 10 species excluded, resulting in a total number of 242 valid mosquito species known to occur in French Guiana. Three nominal species are synonymized, three others are newly described, and a last one is transferred to another informal infrasubgeneric group. Overall, this review also highlights the limits of the use of only bibliographic data when dealing with taxonomically complex groups of insects.